Sustainability reporting and audit reliability: Comparative analysis between financial and non-financial sectors in Nigeria - Legodi, Audrey Hlabisang; Oladejo, Titilayo Moromoke (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study examines the effect of sustainability reporting (SR), measured through environmental, social, and governance (ESG) disclosure, on audit reliability in Nigeria’s financial and non-financial sectors and determine whether the impact differs for the 2 sectors. Audit reliability is proxied by audit effort (ADE) and audit report lag (ARL), capturing the timeliness and intensity of auditing. The study focuses on 24 listed firms 12 banks and 12 manufacturing companies chosen to ensure sectoral comparability and due to the limited number of listed banks with complete data. Using a dynamic panel model estimated through the generalized method of moments (GMM), the results show that SR disclosure significantly increases both ADE and ARL across sectors, with financial firms exhibiting higher audit effort in response to sustainability reporting, while non-financial firms show longer audit report lag, suggesting differences in audit verification intensity and internal control systems. Economically, these findings imply that SR enhances audit reliability, enhances corporate legitimacy and strengthens stakeholder confidence but may increase audit costs and time. The study contributes to the literature by providing sector-comparative evidence from a developing economy, highlighting the role of ESG disclosure in improving audit quality, corporate legitimacy, and investor trust in Nigeria.